Intervention in crisis and early prevention in mental health - Maldonado P., Miguel (2001)
Intervention in crisis and early prevention are two fields in which we have been working for several years in the Psychology service of the Instituto Materno Perinatal, better known as Maternidad de Lima. Two study cases of a critical moment in a family are presented. Their cannot be given a negative value because they refer to a common crisis in the family development. They are about a baby coming to life into an environment whose expectations are already part of the baby´s life and history before being born. Theses constitute a sort of psychological cradle where the baby will feel protect and rest.